Efeito do envelhecimento a 475°C por curtos períodos de tempo nas propriedades mecânicas e na resistência à corrosão dos aços inoxidáveis duplex UNS S32304, UNS S31803 e UNS S32750 - Barros, Artur Pratti de (2016)
This paper studied the effect of exposition to 475°C during short periods of time, in the localized resistance corrosion and in mechanical resistance of steels UNS S32304, S31803 and S32750, the formation of alpha prime phase (α')after exposition to 475°C was followed throughelectrochemical techniques potentiodynamic reactivation double loop (DL-EPR) and electrochemical impedance spectroscopy, beyond the microhardness test.The samples were heat treated at 475°C during 4, 8 and 12 hours to provoke theprecipitation of alpha prime phase. The tests of DL-EPR and electrochemical impedance spectroscopywere performed in 2M H2SO4solution + 0.5 M NaCl + 0.01 M KSCN.Through the tests of DL-EPR was verifieda peak of reactivation only for a sample of steel UND S32304 treated for 8 hours, for the other samples there weren’t a reduction of resistance to corrosion, but,through the analyze of activationcurrentdensity, it was noticed the there was a reduction of resistance to corrosion of the treated samples.The tests of microhardness also showed changes to the heat treated, increasing the values of microhardness related to de condition as received. Andfinally, through the test of electrochemical impedance spectroscopy, it was analyzed the resistance to corrosion located in each situation. The UNS S32304 alloy showed the worst resistance to corrosionand the UNS S32750 alloy showed the best resistance to corrosion